2009
DOI: 10.1093/hmg/ddp117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of interactive networks of gene expression associated with osteosarcoma oncogenesis by integrated molecular profiling

Abstract: Altered gene expression in tumors can be caused by copy number alterations to DNA or mutation affecting coding or regulatory regions of genes. However, epigenetic events may also influence gene expression. Malignant cells can show major disruptions in DNA methylation profiles, which are manifested as aberrant hypermethylation or as hypomethylation of gene promoters, as well as global genomic hypomethylation. In this study we performed integrative whole-genome analysis of DNA copy number, promoter methylation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
107
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 38 publications
12
107
0
Order By: Relevance
“…HDAC9 gain has been described in squamous cell cervical carcinomas (47), and higher HDAC9 expression has been associated with poor prognosis in childhood acute lymphatic leukemias (48). DOCK5, which maps to 8p21.2-p21.3, encodes the dedicator of cytokinesis 5 protein and is recurrently deleted and underexpressed in osteosarcoma (49,50). All of these candidate genes should be further analyzed to explore their potential and specific contributions to PCNSL pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC9 gain has been described in squamous cell cervical carcinomas (47), and higher HDAC9 expression has been associated with poor prognosis in childhood acute lymphatic leukemias (48). DOCK5, which maps to 8p21.2-p21.3, encodes the dedicator of cytokinesis 5 protein and is recurrently deleted and underexpressed in osteosarcoma (49,50). All of these candidate genes should be further analyzed to explore their potential and specific contributions to PCNSL pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…GOLPH3L is located at 1q21.3. It has been reported that 1q21 is amplified in several human malignancies, including rhabdomyosarcoma (16)(17)(18)(19)(20)(21)(22)(23)(24). An amplification of 5p13 has not yet been reported in rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that these histone clusters genes are overexpressed in several types of malignancies. Sadikovic and colleagues performed integrative whole-genome analysis of DNA copy numbers, promoter methylation, and gene expression using 10 osteosarcomas and identified significant changes, including the hypomethylation, gain, and overexpression of histone cluster 2 genes on chromosome 1q21.1-q21.3 (19). Moreover, Perez-Margan and colleagues identified candidate genes related to meningioma recurrence by differential gene expression profiling analyses of 33 original and 7 recurrent meningiomas.…”
Section: Discussionmentioning
confidence: 99%